KONSTRUKSI METODE PENCATATAN AKUNTANSI BERBASIS NILAI BUDAYA ISLAM GORONTALO - Thalib, Mohamad Anwar (Widya Mandala Surabaya Catholic University, 2023)
Research Purpose. The purpose of this study is to formulate how the coachmen practice the method of accounting records based on the cultural values of the Gorontalo people.Research Methods. The paradigm used by this research is Islam with an Islamic ethnomethodology approach.Research Result and Findings. The results show that there are two ways the coachmen practiced the recording method; the first to record the accounting for income, expenses, and savings in memory; record accounts payable on paper. Both of these recording methods are based on the value of responsibility. Parents (the elders) often give advice on this value through lumadu